Elucidating the strain–vacancy–activity relationship on structurally deformed Co@CoO nanosheets for aqueous phase reforming of formaldehyde - Qian, Kaicheng (2022)
Lattice strain modulation and vacancy engineering are both effective approaches to control the catalytic properties of heterogeneous catalysts. Here, Co@CoO heterointerface catalysts are prepared via the controlled reduction of CoO nanosheets. The experimental quantifications of lattice strain and oxygen vacancy concentration on CoO, as well as the charge transfer across the Co-CoO interface are all linearly correlated to the catalytic activity toward the aqueous phase reforming of formaldehyde to produce hydrogen. Mechanistic investigations by spectroscopic measurements and density functional theory calculations elucidate the bifunctional nature of the oxygen-vacancy-rich Co-CoO interfaces, where the Co and the CoO sites are responsible for CH bond cleavage and OH activation, respectively. Optimal catalytic activity is achieved by the sample reduced at 350 °C, Co@CoO-350 which exhibits the maximum concentration of Co-CoO interfaces, the maximum concentration of oxygen vacancies, a lattice strain of 5.2% in CoO, and the highest aqueous phase formaldehyde reforming turnover frequency of 50.4 h-1 at room temperature. This work provides not only new insights into the strain-vacancy-activity relationship at bifunctional catalytic interfaces, but also a facile synthetic approach to prepare heterostructures with highly tunable catalytic activities.